2021
DOI: 10.2196/25704
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning Technologies in Pressure Injury Management: Systematic Review

Abstract: Background Pressure injury (PI) is a common and preventable problem, yet it is a challenge for at least two reasons. First, the nurse shortage is a worldwide phenomenon. Second, the majority of nurses have insufficient PI-related knowledge. Machine learning (ML) technologies can contribute to lessening the burden on medical staff by improving the prognosis and diagnostic accuracy of PI. To the best of our knowledge, there is no existing systematic review that evaluates how the current ML technologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 56 publications
1
33
0
1
Order By: Relevance
“…Some studies focused on the analysis of algorithms or models for predicting PU risk, usually having an associated risk indicator as an output (e.g., [14]). The study presented in [13] partially addresses this issue. In this study, the authors analyze works that used ML technologies with the aim of contributing to lessen the burden on medical staff by improving the prognosis and diagnostic accuracy of PU.…”
Section: Review Analysis/resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Some studies focused on the analysis of algorithms or models for predicting PU risk, usually having an associated risk indicator as an output (e.g., [14]). The study presented in [13] partially addresses this issue. In this study, the authors analyze works that used ML technologies with the aim of contributing to lessen the burden on medical staff by improving the prognosis and diagnostic accuracy of PU.…”
Section: Review Analysis/resultsmentioning
confidence: 94%
“…Identified Opportunities and Future Research [13] Studies were classified and organized into three groups: 12 (38%) reported using ML technologies to develop predictive models to identify risk factors, 11 (34%) reported using them in posture detection and recognition, and 9 (28%) reported using them in image analysis for tissue classification and measurement of PU wounds.…”
Section: Review Analysis/resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study presented in [7] is focused on ML applications for PU prevention. In this study, the authors analyze works that use ML technologies to lessen the burden of medical staff by improving the prognosis and diagnostic accuracy of PU.…”
Section: Review Analysis/resultsmentioning
confidence: 99%
“…To identify the state-of-the-art approaches that use software to assist health professionals in PU prevention support. 36 1989-2014 [7] 2021…”
Section: Reviewmentioning
confidence: 99%